2018
DOI: 10.1021/acs.jpcc.8b01529
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Formation vs Molecular Exchange in Organic Heterostructures: Strong Impact of Subtle Changes in Molecular Structure

Abstract: Organic heterostructures are a central part of a manifold of (opto)electronic devices and serve a variety of functions. Particularly, molecular monolayers on metal electrodes are of paramount importance for device performance as they allow tuning energy levels in a versatile way. However, this can be hampered by molecular exchange, i.e., by interlayer diffusion of molecules toward the metal surface. We show that the organic−metal interaction strength is the decisive factor for the arrangement in bilayers, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 98 publications
6
62
0
Order By: Relevance
“…In the present case, no information on the surface tension of 2H-TPP is available. In line with earlier studies on exchange processes in organic bilayers, 10,2730 it seems reasonable to assume that the determining factor for the replacement of [C 8 C 1 Im][PF 6 ] by 2H-TPP at the IL/metal interface is the stronger binding of porphyrin to the metal surface.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In the present case, no information on the surface tension of 2H-TPP is available. In line with earlier studies on exchange processes in organic bilayers, 10,2730 it seems reasonable to assume that the determining factor for the replacement of [C 8 C 1 Im][PF 6 ] by 2H-TPP at the IL/metal interface is the stronger binding of porphyrin to the metal surface.…”
Section: Resultssupporting
confidence: 69%
“…They found that P2O is exchanged by Cu-Pc on the Ag(111) surface, whereas for P4O, no exchange occurs, that is, Cu-Pc remains on top of the P4O layer. 27…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to molecular exchange and preferential adsorption processes after sequential deposition of two different ILs on Ag(111) [81,82], exchange processes have also been reported for organic bilayers on metals involving porphyrins and related aromatic molecules [156][157][158][159][160][161][162][163][164]. These investigations highlight the importance of the strength of the organic-metal interaction and its correlation to the stability and arrangement in stacked multilayer architectures [156,161,162,[164][165][166][167][168][169][170]. Although combinations of porphyrins and ILs were already realized for catalysis [171] and dye-sensitized solar cell technologies [40,41], dedicated interface studies of porphyrin/IL hybrid systems are still missing.…”
Section: Replacement Of Ionic Liquids By Porphyrins At Metal Interfacesmentioning
confidence: 85%
“…We superimposed the STM image by the contours of the two molecules in the unit cell as well as the adsorbate lattice as determined by LEED. A DBP molecule is characterized by four bright protrusions, which correspond to the phenyl substituents oriented nearly perpendicular to the aromatic backbone and two smaller double lobes which correspond to the bisbenz [5,6]indeno end groups [26].…”
Section: Lateral Structurementioning
confidence: 99%
“…Some applications, however, require to preserve the intrinsic properties of the molecules such as the typically rather narrow optical absorption and/or emission bands. To achieve this, one needs to electronically decouple the molecules from the substrate, which can be achieved through different ways such as the usage of wide-band-gap insulator thin films (e.g., oxides, alkali halides) [ 3 4 ], a molecular spacer layer [ 5 6 ], or sp 2 -hybridized two-dimensional interlayers (e.g., graphene and hexagonal boron nitride (h-BN)) [ 7 8 ]. The advantageous properties of an h-BN monolayer on metal single crystals are the high crystal quality, chemical inertness and the wide band gap of approx.…”
Section: Introductionmentioning
confidence: 99%